The Correlation Between Wall Shear Stress and Plaque Composition in Advanced Human Carotid Atherosclerosis - Moerman, A. M.; Korteland, S.; Dilba, K.; van Gaalen, K.; Poot, D. H. J.; van Der Lugt, A.; Verhagen, H. J. M.; Wentzel, J. J.; van Der Steen, A. F. W.; Gijsen, F. J. H.; Van der Heiden, K. (Frontiers in Bioengineering and Biotechnology, 2022)
The role of wall shear stress (WSS) in atherosclerotic plaque development is evident, but the relation between WSS and plaque composition in advanced atherosclerosis, potentially resulting in plaque destabilization, is a topic of discussion. Using our previously developed image registration pipeline, we investigated the relation between two WSS metrics, time-averaged WSS (TAWSS) and the oscillatory shear index (OSI), and the local histologically-determined plaque composition in a set of advanced human carotid plaques. Our dataset of 11 carotid endarterectomy samples yielded 87 histological cross-sections, which yielded 511 radial bins for analysis. Both TAWSS and OSI values were subdivided into patient-specific low, mid and high tertiles. This cross-sectional study shows that necrotic core (NC) size and macrophage area are significantly larger in areas exposed to high TAWSS or low OSI. Local TAWSS and OSI tertile values were generally inversely related, as described in literature, but other combinations were also found. Investigating the relation between plaque vulnerability features and different combinations of TAWSS and OSI tertile values, revealed a significantly larger cap thickness in areas exposed to both low TAWSS ánd low OSI. In conclusion, our study confirmed previous findings, correlating high TAWSS to larger macrophage areas and necrotic core sizes. In addition, our study demonstrated new relations, correlating low OSI to larger macrophage areas, and a a combination of low TAWSS ánd low OSI to larger cap thickness.